Case Report: Recurrence of Positive SARS-CoV-2 Results in Patients Recovered From COVID-19 - Zhang, Ren-zi; Deng, Wang; He, Jing; Song, Yu-yan; Qian, Chun-fang; Yu, Qian; Wang, Dao-xin (Frontiers in Medicine, 2020)
Background: Coronavirus disease 2019 (COVID-19) is spreading throughout the world. Limited data are available for recurrence of positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) results in patients with long duration of COVID-19. Methods: We reported four cases recovered from COVID-19 with recurrence of positive SARS-CoV-2 results during the long-term follow-up. Results: The four patients recovered from COVID-19 showed recurrence of positive SARS-CoV-2 results for more than 120 days with no symptoms and normal chest CT scan. Conclusions: The dynamic surveillance of SARS-CoV-2 by nucleic acid detection and serological assays is important for asymptomatic patients who might be potentially infectious.